PENGARUH PENERAPAN PROMOSI DAN DEMOSI TERHADAP PRESTASI KERJA KARYAWAN PADA MASTER KREDIT CABANG MEDAN - Noor Aini Pratita Adianti Linearita; yasmin chairunisa muchtar (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT   The issue  of this research is to know whether the implementation of promotion and demotion’s effect are positive and significant towards the employee’s achievement at the Master Kredit Cabang Medan. The collection of primary data is done through a questioner that propagated to staff employees / fixed employee’s. The sampling method was used saturated sampling / census which the population of this research is 54 staff / employees remain on marketing division and collection division in Master Kredit Cabang Medan. The method used was descriptive quantitative analysis by using multiple linear regression for the hypothesis. The results showed that simultaneously promotion and demotion variable’s affect the employee’s achievement variable in Mater Kredit Cabang Medan positively and significant. By the t test for promotion influential positively and  significantly towards the employee’s achievement at the Master Kredit Cabang Medan. While t test of demotion influential positively and significant towards the employee’s achievement at the Master Kredit Cabang Medan.   Keywords: Promotion, Demotion, Employee’s Achievement.